Confiscation of Central Bank Assets and Possible Implications on the Law of State Immunity - Lindblad,Rebecca (2025)
This thesis examines the scope of the law of State immunity from enforce-ment, with the intention of determining if the frozen assets and reserves of the Central Bank of Russia can be confiscated without implicating State immuni-ty. State immunity from enforcement has its legal basis in customary interna-tional law and is generally understood to protect State property from being subjected to pre- or post-judgment measures of constraint, including attach-ment and execution, but its exact scope is widely debated. Although sanctions against central banks is not unprecedented, the scope of the sanctions imposed against the Central Bank of Russia after Russia’s inva-sion of Ukraine is unparalleled, in terms of the amount of assets these sanc-tions implicate. These sanctions have in the past primarily consisted of assets freezes, but in recent years States have proposed and adopted regulations that provide a national or regional basis for confiscation of the frozen assets. Due to the political pressure and public attention such suggestions and actions have retained, and the flexibility of customary international law, it is of importance to evaluate whether a confiscation of the Central Bank of Russia assets would be permittable under the law of State immunity from enforcement. The thesis employs a legal doctrinal method, and thus systemizes and analyzes recognized legal sources of the law of State immunity to clarify the scope of State immunity from enforcement. Since State immunity is based in customary law, the thesis primarily examines judgments from national, regional and in-ternational courts, domestic legislation and the International Law Commis-sion’s attempt to codify said customary law in the United Nations Convention on Jurisdictional Immunities of States and Their Property. The thesis also applies literature to interpret the content of customary law. The thesis finds that central banks are granted an extensive protection from enforcement measures under the law of State immunity, and that particularly central bank assets that serve sovereign monetary purposes are provided with absolute immunity from enforcement measures before foreign courts. In addi-tion, the thesis examines two potential exceptions to State immunity, applica-ble when the foreign State is designated as a supporter of terrorism or has violated peremptory norms, but concludes that no such exceptions exist under the customary international law on State immunity. Lastly, the thesis examines if State immunity from enforcement extends to non-judicial measures of con-straint, including inter alia executively ordered sanctions. The thesis finds that a confiscation of the Central Bank of Russia assets, if undertaken inde-pendently of any court proceedings, ought to be permitted according to the rationale of State immunity, however due to the lack of State practice, the le-gality of this type of confiscation cannot be determined for certain.